Studi Analisis Kesetaraan Sosial bagi Penyandang Disabilitas pada QS An-Nur 61 dan QS Abasa 1-3 dalam Kitab Tafsir Ibnu Katsir - Sinaga, Sania Arisa (ANWARUL, 2023)
This research examines the analysis of social equality for persons with disabilities in the Qur'an Surah An-Nur: 61 and the Qur'an Surah Abasa: 1-3 in the book of Ibnu Katsir's commentary. This type of research is qualitative research which describes data using a series of sentences. The method used in this research is descriptive method. The results of this study indicate that persons with disabilities in the view of the Al-Quran are studied in the interpretation, namely, (Tafsir Ibnu Katsir). Persons with disabilities in the Al-Quran show human deficiencies biologically or physically and examples/parables. As for persons with disabilities, in the view of the Koran, this refers to persons with physical disabilities, namely: Acting the same or being tolerant towards others, not discriminating, Providing relief not to carry out perfectly the obligations that guide the five senses and their physical members, not discriminating, have the right to choosing and continuing friendships and being allowed not to join the war. Meanwhile, indirectly in other surahs it shows attitudes towards persons with disabilities, namely not discriminating, such as not making fun of, criticizing either in the form of derogatory actions or remarks and also what distinguishes individuals is their faith and piety.